My social media for seniors - Miller, Michael 1958- (Que, 2020)
My Social Media for Seniors Step-by-step instructions for the tasks you care about most Large, full-color, close-up photos show you exactly what to do Common-sense help whenever you run into problems Tips and notes to help you along the way Learn how to get the most out of social media! We've identified the essential skills you need to stay connected with the people you care about; reconnect with old friends and classmates; and share your life with loved ones near and far. Our crystal-clear instructions respect your smarts but never assume you're an expert. Big, colorful photos on nearly every page make this book incredibly easy to read and use! · Learn the pros and cons of social media and how to use it safely · Find out what to share-and what not to share-on social media · Distinguish between fake news and real news online · Use social media to find friends, family, schoolmates, and co-workers · Keep in touch with friends and family on Facebook® · Save and share interesting images on Pinterest"!· Connect with people and businesses on LinkedIn® · Tweet and retweet on Twitter"!· Share photos on Instagram"!· Use Skype to participate in video chats with friends and family members
Previous edition published: 2018. - "AARP, real possibilities.". - "Covers Facebook, Instagram, LinkedIn, Pinterest, and Twitter"--Cover. - Includes index. - Online resource; title from title page (Safari, viewed August 13, 2019)
Keywords: Computers and older people; Online social networks; Social media; Social Media; Ordinateurs et personnes âgées; Réseaux sociaux (Internet); Médias sociaux; social media